3D lattice meso-scale modelling of the effect of lateral compression on tensile fracture processes in concrete. (1st February 2023) - Grassl, Peter
Abstract: The effect of lateral compressive stresses on the cracking process in tension is rarely considered in fracture models for quasi-brittle materials such as concrete. In this study, this effect is investigated by means of a meso-scale lattice approach in which a damage-plasticity constitutive model is combined with an auto-correlated random field of strength and fracture energy. In the first part of the analyses, the lattice approach is compared with experimental results in tension and compression, which shows a good agreement between simulations and experiments. Then, cells with periodic lattices and periodic boundary conditions are loaded in two steps. Firstly, compression is applied. Next, the cell is extended in the lateral direction while keeping the compressive stress constant. It is shown that with increasing compressive stress applied, the post-peak energy dissipation in tension increases. Postprocessing of the results of the analyses reveals that this increase is due to greater frictional energy dissipation and greater number of cracks than for pure tension. Highlights: 3D damage-plasticity lattice approach with auto-correlated random field Comparison of lattice model with tension, uni- and biaxial compression experiments Meso-scale analyses of the effect of lateral compression on tensile fracture Evaluation of dissipated energy and width of the fracture process zone